2020
DOI: 10.1021/acs.orglett.0c00296
|View full text |Cite
|
Sign up to set email alerts
|

M[TPP]Cl (M = Fe or Mn)-Catalyzed Oxidative Amination of Phenols by Primary and Secondary Anilines

Abstract: Iron- and manganese-catalyzed para -selective oxidative amination of (4-R)phenols by primary and secondary anilines was developed. Depending on the identity of the R group, the products of this efficient reaction are either benzoquinone anils (C–N coupling) that are produced via a sequential oxidative amination/dehydrogenation (R = H), oxidative amination/elimination (R = OMe) steps, or N , O -biaryl compounds (C–C coupling) that are formed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…The formation of an intense purple color confirmed the IAd formation. Reported spectra were compatible with those available in the literature, obtained through a different synthetic pathway [54].…”
Section: Synthesis Of the Indoaniline Derivativesupporting
confidence: 61%
“…The formation of an intense purple color confirmed the IAd formation. Reported spectra were compatible with those available in the literature, obtained through a different synthetic pathway [54].…”
Section: Synthesis Of the Indoaniline Derivativesupporting
confidence: 61%
“…Newly synthesized compound was characterized by 1 Reported spectra were compatible with those available in the literature, obtained through a different synthetic pathway [54].…”
Section: Synthesis Of the Indoaniline Derivativementioning
confidence: 92%
“…9f , 10 Lately, our group has developed an M[TPP]Cl (M = Fe or Mn, TPP = 5,10,15,20-tetraphenyl-21H,23H-porphine)-catalyzed para -selective oxidative amination of phenols by primary and secondary anilines ( Scheme 1 B). 11 We have demonstrated that, depending on the identity of the phenolic para -R group, the products of this coupling are either benzoquinone anils (when R = H or OMe) or N , O -biaryl compounds (when R = alkyl). In a previous paper, we developed a two-step synthesis of optically pure NOBIN derivatives.…”
Section: Introductionmentioning
confidence: 92%
“…5b However, the partial order for the phenolic component is no longer zero when the catalyst has a limited number of vacant sites, as exemplified by Katsuki [(Fe[μ-OH][salen]) 2 catalyst] 13 and Pappo [Fe[phosphate] 3 catalyst] ( Figure 1 B). 5c Furthermore, when the reaction is mediated by Fe[TPP]Cl, which has only a single axial position available for binding, the coupling takes place between a ligated phenoxyl radical and a liberated phenoxyl 5a or an anilino radical 11 by an outer-sphere radical–radical coupling mechanism ( Figure 1 C). These studies show that the coupling mechanism changes as a function of the iron coordination sphere.…”
Section: Introductionmentioning
confidence: 99%